2017
DOI: 10.3233/jad-170402
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Arterial 4D Flow in Individuals with Mild Cognitive Impairment is Associated with Cognitive Performance and Amyloid Positivity

Abstract: It is becoming increasingly recognized that cerebrovascular disease is a contributing factor in the pathogenesis of Alzheimer’s disease (AD). A unique 4D-Flow magnetic resonance imaging (MRI) technique, phase contrast vastly undersampled isotropic projection imaging, (PC VIPR), enables examination of angiographic and quantitative metrics of blood flow in the arteries of the Circle of Willis within a single MRI acquisition. Thirty-eight participants with Mild Cognitive Impairment (MCI) underwent a comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…51 While 4D flow MRI studies have correlated higher pulsatility of intracranial arteries and veins with AD pathology. 1113,52 Furthermore, vessel pulsatility has been speculated as a driver of glymphatic flow, as the motive force for perivascular drainage of interstitial fluid, Aβ, and other soluble metabolites. 53,54 Cardiac pulsations may also contribute to clearance of soluble metabolites from the brain by mixing and dispersion effects.…”
Section: Discussionmentioning
confidence: 99%
“…51 While 4D flow MRI studies have correlated higher pulsatility of intracranial arteries and veins with AD pathology. 1113,52 Furthermore, vessel pulsatility has been speculated as a driver of glymphatic flow, as the motive force for perivascular drainage of interstitial fluid, Aβ, and other soluble metabolites. 53,54 Cardiac pulsations may also contribute to clearance of soluble metabolites from the brain by mixing and dispersion effects.…”
Section: Discussionmentioning
confidence: 99%
“…They found that lower mean flow of the middle cerebral arteries (MCAs) and internal carotid arteries (ICAs) was associated with greater brain atrophy, as was increased MCA stiffness (represented as Gosling’s Pulsatility Index equation, PI = (flow max – flow min )/flow mean ); they also found decreased mean flow in the ICAs was associated with lower amyloid beta in the CSF. The same group carried out a similar study two years later, 12 with subjects undergoing a neuropsychiatric battery and lumbar puncture (for CSF assay). They found an association between ICA and MCA mean flow and executive functioning performance, as well as evidence of an association between decreased blood flow and amyloid beta deposition across 38 MCI subjects, correcting for age and sex.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, blood samples can be very easily collected from the patients, while the collection of the CSF samples needs procedures that require lumber punctures. Therefore, it becomes a great drawback of the CSF biomarkers in comparison to the blood biomarkers [75,76] due to its stability. However, assaying Aβ proteins in the blood becomes difficult when other proteins present in the blood interfere with the procedure, or the sample can even undergo photolytic reactions [18].…”
Section: Cerebrospinal Fluid T-taumentioning
confidence: 99%